Stewardship and administrative capacity in green public procurement in the Czech Republic: Evidence from a large-N survey - Michal Plaček; Vladislav Valentinov; Cristina del Campo; Gabriela Vaceková; František Ochrana; Markéta Šumpíková (Environmental Sciences Europe, 2021)
Background: The uptake of green public procurement in the Czech Republic is known to lag behind the European standards. We trace this condition back to the adverse effects of a specific type of decision-making trade-off faced by the Czech public procurement officials, namely the trade-off between stewardship and administrative compliance. The trade-off means that public procurers are aware of administrative risks and complications attendant on the conscientious non-perfunctory implementation of green public procurement. Results: The overall result is that public procurers ultimately come to prioritize the contract criterion of the lowest price over ecological criteria. The existence of this trade-off has been generally confirmed by the results of a unique large-N survey of more than 1100 respondents from a group of local public officials and mayors in the Czech Republic. Conclusion: We have found that the decision-making of Czech public procurers is affected by the trade-off between stewardship and administrative compliance, which turn out to be mutually conflicting goals. On the one hand, many public procurers do possess a stewardship motivation that shapes their positive attitude to GPP. On the other hand, they are painfully aware of, and seek to forestall, administrative risks and complications attendant on the conscientious, i.e., non-perfunctory, implementation of GPP.
Keywords: 330; green public procurement; stewardship; administrative capacity; large-N survey; Czech Republic